DIGITAL TRANSFORMATION’S FINANCIAL IMPACT ON UZBEKISTAN GOVERNMENT AGENCIES - Saidov Saidahrorxo'ja Nosirxo'jayevich (Prospects for innovative technologies in science and education, 2026)
Uzbekistan's government launched an ambitious digital transformation under the "Digital Uzbekistan-2030" strategy. This effort targeted deep inefficiencies across thousands of public agencies. Paper-based processes created massive waste, long delays, and low citizen satisfaction. The study examined financial returns from key platforms while developing a national scaling model.